New distribution records of Compositae from Aguascalientes, Mexico - Garcia Regalado, Gerardo (Instituto de Ecología, A.C., 1999)
A floristic survey of the family Compositae from Aguascalientes state, Mexico, has been performed. This survey has resulted in new records of 64 genera and 103 species for the state. Some of the specimens were collected from localities of difficult access. The taxa representing new records are listed along with distributional data.